The examinations field of action: interim evaluation and future prospects - Lennartz, Dagmar [Verfasser] (My University, 2007)
"Examination can be a motive force and a supporter of system development but they can also be a restraint and a drag on it. In the past 30 years, examinations have placed both of those roles for "Training in Occupations". In the first ten years the were a central means of developing quality assurance in vocational education and training, but subsequently they increasingly came under fire from all sides. The dual system of vocational education and training was undergoing allround modernisation, but there was little change in examination practice. However, things have begun to move in the field of vocational examinations in the last five years. Innovations in examination models and examination structures have largely exhausted the possibilities of the traditional examination system. The changes in the examination system introduced up to now are therefore not the end but rather the beginning of an overdue process of reform." (BIBB)
Erstveröffentlichung der englischen Version des Artikels in: BWP Special Edition 2005, S. 32-37
Keywords: L 7 Prüfungen; L 7.2 Prüfungsformen; S 1.3.1 Ausbildung im Dualen System; Prüfung; Reform; Berufsausbildung; Duales System